Slavery in early America as Portrayed in Toni Morrison’s A Mercy and other novels - KPOHOUE, FERDINAND (My University, 2018)
Since the publication of her debut novel in 1970, Toni Morrison is interested in the black community in America characterized by community life, gossips, and solidarity. However this community is victim of slavery and segregation due to skin complexion. The publication of A Mercy in 2008 has provided a new dimension to the scope of her literary motivation. She has gone deep in the history of America at the beginning of the settlement of Europeans in the 1680’s to uncover the universal form of slavery without racism including Europeans, native Americans, and blacks. They were servants owned by the gentry that submitted them to harsh work and difficult conditions. In A Mercy there exist slaves, indentured servants, and freed blacks. The objective of this research paper is to explore the slavery system without racial pigmentation unknown or forgotten in America. As a matter of fact, Jacob Vaark’s farm is a sample selected by Morrison to portray the bondage pattern in the 1680’s. Messalina is shortened (Lina), she is an Indian native on the farm. Florens is offered by her mother to pay the debt of her master. Florens’s mother is regularly raped, she does not want her daughter to be raped by her master. The blacksmith is a free black man, Willard and Scully are Vaark’s Europeans indentured servants, etc. They all work on the same farm together with Vaark’s mailed wife Rebekka. Vaark’s servants are not happy because they are not free but they do not suffer racial discrimination. They are not happy because the middle passage is unbearable, some prefer to end up in the mouth of the sharks following their ship, but they are not stereotyped as they are blacks, Indians or Europeans. They are servants or free workers.
Keywords: Slavery; Indentured servants; free blacks; race; discrimination.